Lung cancer and kidney injury: an updated review - Bhargav Patel; Mohammad Ebrahimi Kalan; Maryam Khosravian; Audrey Tolouian; Ramin Tolouian; Mahnaz Aboufazeli; Masoumeh Asgharpour; Amirhesam Alirezaei (Society of Diabetic Nephropathy Prevention, 2021)
Lung cancer is the leading cause of cancer deaths worldwide, accounting for an estimated 1.8 million deaths. Lung cancer is also the most common primary cancer leading to soft tissue (ST) metastasis. Renal disease may occur as a direct or indirect consequence of the cancer itself (e.g., postrenal obstruction, compression, or infiltration), its treatment (e.g., radiotherapy or chemotherapy), or its related complications (e.g., opportunistic infection). Existing evidence shows that the most frequent primary solid tumor responsible for renal metastasis is pulmonary carcinoma, followed by gastric, breast, soft tissue, and thyroid carcinomas. Chronic kidney disease is a potential risk factor in the survival of patients with lung cancer. In this review, we will discuss causes of kidney injury in relation to lung cancer, potential mechanisms of kidney injury, and treatment options.